An Efficient Extraction, Characterization and Antioxidant Study of Polysaccharides from Peucedani Decursivi Radix - Qian Li; Zeyu Li; Chaogui Hu; Chenyue Wang; Feng Yang; Xiaoqin Ding (Plants, 2025)
Hot water extraction (HE), enzyme-assisted hot water extraction (EAHE), ultrasonic-assisted extraction with NADES (UAE-NADES) and ultrasonic-assisted extraction with NADES and enzyme pretreatment (UAE-NADES-E) were employed to extract polysaccharides from Peucedani Decursivi Radix (PDR) and their structures were characterized for the first time. UAE-NADES-E was found to be the most effective extraction method, and the extraction process was optimized by Box–Behnken design (BBD)-response surface methodology (RSM) experiments. The optimal extraction process was determined by using a NADES system with a molar ratio of betaine to 1,3-butanediol of 1:3, a water content of 30%, a liquid/solid ratio of 40:1 mL/g, an ultrasound time of 30 min, an ultrasound temperature of 45 °C and an alcohol precipitation time of 6 h; the polysaccharide extraction yield reached 19.93%. Further, the structures of polysaccharides from PDR extracted by the above four methods were characterized by FT-IR, SEM, gel and anion-exchange chromatography. Eight monosaccharides were detected in the PDR polysaccharides extracted by the four methods. The PDR polysaccharides extracted by the UAE-NADES-E method had lower molecular weights compared with those extracted by the other methods. Moreover, the PDR polysaccharides exhibited obvious antioxidant activity, as revealed by DPPH, ABTS+ and hydroxyl radical scavenging experiments, meaning they have the potential to be developed as natural antioxidants.